The Dutch Disease Syndrome Side Effects in Manufacturing Employment: A VAR Analysis of the Azerbaijan Economy - Ibrahim Niftiyev (Proceedings of 9th International Multidisciplinary Conference on Economics, Business, Technology and Social Sciences: 14-15 May, 2022, Istanbul, Turkey, 2022)
After the painful transition process from a command economy to a market economy, Azerbaijan used its rich hydrocarbon resources to promote economic growth and development. As a result, national income and per capita income soared, infrastructure improved, and poverty was reduced. However, Azerbaijan's economy seems to have been caught up in the negative effects of the oil boom. In other words, non-oil tradeable sectors such as manufacturing have not been able to build on the success and gain a high share of output, employment, and exports due to the increase in the real effective exchange rate (REER) and domestic prices. So far, the literature on studies of Dutch disease in the Azerbaijani economy has focused on highly aggregated data without properly separating the effects of Dutch disease, namely resource movement and spending effects. In this paper, the effects of resource movement were examined using manufacturing employment with a standard unrestricted vector autoregression (VAR). However, to ensure analytical accuracy, the spending effect was also considered. The results show that manufacturing employment responds positively to mining employment. However, when employment in the service sector increases, manufacturing employment shrinks, which is also negatively affected by oil prices and the appreciation of the REER. These results may be useful for policymakers to neutralize the impact of Dutch disease to ensure sustainable development goals and promote export-led growth policies in the manufacturing sector.
Keywords: C32; F41; Q32; Q33; 330; Azerbaijan economy; Dutch disease; employment; labor resources; manufacturing; natural resource curse; unrestricted VAR